Reorientasi Kebijakan UMKM di Era Asia China Free Trade Area (ACFTA) - Suyatna, Hempri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2010)
Most of Small Medium Enterprises (SMEs) worried after government implementing the Asia China Free Trade Area (ACFTA). This agreement pushed down the import tariff from five percent to zero percent. Chinaâs products and local product compete in market without government protection. Chinaâs products will dominate market share due to the lowness of local products competitiveness. In several years, deindustrialization potentially happens in Indonesia. Government should reorient the SMEs development policy to minimize negative impact of ACFTA. It can be done by supporting local potential commodities, revitalizing capital loan policy, and synergy between government and others stakeholders to develop SMEs.